Characterization of Schu S4 aro mutants as live attenuated tularemia vaccine candidates - Aimee L. Cunningham (Taylor & Francis Group, 2020)
There is a need for development of an effective vaccine against Francisella tularensis, as this potential bioweapon has a high mortality rate and low infectious dose when delivered via the aerosol route. Moreover, this Tier 1 agent has a history of weaponization. We engineered targeted mutations in the Type A strain F. tularensis subspecies tularensis Schu S4 in aro genes encoding critical enzymes in aromatic amino acid biosynthesis. F. tularensis Schu S4ΔaroC, Schu S4ΔaroD, and Schu S4ΔaroCΔaroD mutant strains were attenuated for intracellular growth in vitro and for virulence in vivo and, conferred protection against pulmonary wild-type (WT) F. tularensis Schu S4 challenge in the C57BL/6 mouse model. F. tularensis Schu S4ΔaroD was identified as the most promising vaccine candidate, demonstrating protection against high-dose intranasal challenge; it protected against 1,000 CFU Schu S4, the highest level of protection tested to date. It also provided complete protection against challenge with 92 CFU of a F. tularensis subspecies holarctica strain (Type B). Mice responded to vaccination with Schu S4ΔaroD with systemic IgM and IgG2c, as well as the production of a functional T cell response as measured in the splenocyte-macrophage co-culture assay. This vaccine was further characterized for dissemination, histopathology, and cytokine/chemokine gene induction at defined time points following intranasal vaccination which confirmed its attenuation compared to WT Schu S4. Cytokine, chemokine, and antibody induction patterns compared to wild-type Schu S4 distinguish protective vs. pathogenic responses to F. tularensis and elucidate correlates of protection associated with vaccination against this agent.